Pengaruh remunerasi dan disiplin kerja terhadap kinerja pegawai pada Badan Perencanaan Pembangunan Daerah Kabupaten Lampung Tengah - Silitonga, Doni Tri Saputra; Iskandar, Iskandar (Jurnal Manajemen Strategi dan Aplikasi Bisnis, 2024)
This research investigates the impact of remuneration and work discipline on employee work quality at the Regional Development Planning Agency (Bappeda) of Central Lampung Regency. This experiment uses multiple linear regression to carry out the analysis. This experiment took 41 ASN staff of Bappeda Central Lampung Regency as samples using the "census sampling" technique. At the same time, data were obtained through observation with a Likert questionnaire. The results of this experiment show that remuneration and Work Discipline have a relatively significant positive impact on the Quality of Employee work. The combination of independent variables included in the model explains 77% of the coefficient of determination of the variation in Employee Performance. This research contributes to understanding the perceptions and views of employees on the issues studied, as well as providing a basis for decision-making and formulating more effective policy recommendations for the Regional Development Planning Agency. It is concluded that fair compensation and the implementation of effective work discipline positively impact the motivation, productivity, and quality of work of Bappeda employees in Central Lampung Regency.